Extremely periodic pulsating aurora observed near L=6: A new type pulsating aurora - Sato, Natsuo; Nagato, Takeshi; Saemundsson, Thorsteinn (National Institute of Polar Research, 1999)
P(論文) Extremely periodic pulsating aurora, a new type pulsating aurora, was detected by three photometers (directing towards the zenith and 45° N and S in the meridian plane, for 427.8 nm emission) at Husafell in Iceland on 18-19 December 1985. We examined the characteristics of the pulsating auroras and their relationship to magnetic pulsations using the data obtained in Iceland and Syowa Station, the geomagnetically conjugate pair station in Antarctica. The characteristics of this event are as follows; 1) extremely regular periodic pulsating auroras with the frequency of -50 mHz were observed simultaneously on the 3 photometers, 2) the periodicity of the pulsation was extremely high, and the Q-value showed more than 20, 3) the intensity variation among the 3 photometers occurred with excellent coherency and simultaneously without time lag, suggesting that these pulsating auroras were not of a propagating type but a standing type, 4) there are no correlation between the optical pulsating auroras and magnetic pulsations on the ground. These characteristics suggest that the extremely periodic pulsating aurora on this event is not a common (popular) pulsating aurora but an exceptional type pulsating aurora which would occur under a certain condition in the magnetosphere. departmental bulletin paper